Security And The Challenges Of Securing Nigerian State (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Nigeria, like most developing States is still grappling with the task of nation – building, responsive democratic order and a just and secured polity. The task over the years has remained arduous and seemingly illusive. Presently, the menance of Boko Haram, the marauding herdsmen militancy, the new face of militancy in the Niger Delta, the spate of kidnappings, armed robberies, and ethno-regional intolerance, the vociferous separatist agitations in the South-East and South-South and the deteriorating living conditions have continued to create survival, stability and security challenges and threaten the very existence of Nigeria as a federation. Against this backdrop, this paper therefore attempts to identify some of the emerging trends of security challenges in Nigeria with a view to diagnosing their causes and examining their implications on the corporate existence of Nigeria. This paper adopted the analytical method and relied on the natural theory of state to posit that the solution to the disturbing trend of security challenges in Nigeria is employment generation and genuine implementation of poverty alleviation programmes in the polity